2016
DOI: 10.1158/1538-7445.am2016-545
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 545: Differential regulation of human T-cells by TGR-1202, a novel PI3Kδ inhibitor

Abstract: INTRODUCTION: TGR-1202 is a novel, next-generation PI3Kδ inhibitor presenting significant structural and pharmacological differences from prior small-molecule PI3Kδ inhibitors. TGR-1202 has high clinical efficacy in treatment of B cell malignancies with a substantially differentiated adverse event profile compared to previous PI3Kδ inhibitors, specifically concerning hepatotoxicity or colitis which have been minimal or non-existent. It has been postulated that these effects may be due to T cell immune-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This may be related to increased specificity for the d isoform and subsequently less perturbation of regulatory T cells. [47][48][49] Anti-CD20 inhibition Further study with anti-CD20 agents is being pursued, given nonoverlapping toxicity profiles and possible synergistic efficacy. Obinutuzumab is a novel glycol-engineered type 2 anti-CD20 monoclonal antibody demonstrating enhanced antibody-dependent cellular cytotoxicity and phagocytosis as well as increased direct cell death compared with rituximab.…”
Section: Case 2 Presentationmentioning
confidence: 99%
“…This may be related to increased specificity for the d isoform and subsequently less perturbation of regulatory T cells. [47][48][49] Anti-CD20 inhibition Further study with anti-CD20 agents is being pursued, given nonoverlapping toxicity profiles and possible synergistic efficacy. Obinutuzumab is a novel glycol-engineered type 2 anti-CD20 monoclonal antibody demonstrating enhanced antibody-dependent cellular cytotoxicity and phagocytosis as well as increased direct cell death compared with rituximab.…”
Section: Case 2 Presentationmentioning
confidence: 99%
“…60 Our group subsequently described the differential effect of TGR-1202 61,62 in normal human T cells and murine CLL T cells compared with idelalisib and duvelisib. 63,64 Treg numbers and function were depleted by all 3 inhibitors, but were maintained closer to normal levels after TGR-1202 treatment. These data are of relevance to determining why this inhibitor causes fewer incidences of SAEs in patients.…”
Section: Pi3k Inhibitors and Toxicitymentioning
confidence: 89%
“…In a real-world experience, Bange et al demonstrated durable treatment responses after toxicity related discontinuation of idelalisib [ 65 ]. Most of the treatment-limiting toxicities are immune-mediated and depend on Tregs depletion, mediated by PI3Kδ inhibition [ 66 ]. Based on this evidence, it is reasonable to speculate that intermittent dosing schedules with drug free intervals could allow Tregs recovery, thus hopefully improving tolerability of existing PI3Kδ inhibitors.…”
Section: Overcoming Pi3k Inhibitors Treatment Challengesmentioning
confidence: 99%